THE INFLUENCE OF GLOBAL ENGLISH INTERNET SLANG ON LOCAL LANGUAGES (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The rise of global online communication has accelerated the spread of English internet slang into local languages, including Uzbek. This paper examines the sociolinguistic processes through which English informal digital vocabulary enters non-English linguistic systems, influences communication strategies, and reshapes youth identity. Drawing on theoretical perspectives from language contact, borrowing, and globalization, as well as illustrative examples from English and Uzbek, the paper analyzes direct borrowing, hybridization, semantic shifts, and calques. I also present my own interpretation of whether this influence enriches or threatens local linguistic and cultural ecosystems. The findings suggest that although concerns about linguistic purity persist, English internet slang functions as a dynamic force that contributes to linguistic innovation in multilingual digital spaces.